PENGUATAN KETERAMPILAN SOSIAL PADA MAHASISWA GUGUS LATIH ILMU SOSIAL UNIVERSITAS NEGERI SEMARANG TAHUN 2020-2021 (Sosiolium: Jurnal Pembelajaran IPS, 2022)
Students are expected to be able to develop social skills as a provision for the next world of work. Students can develop social skills through campus organizations. The Social Sciences Training Group is an organization that is developing in the field of scouting education at the Faculty of Social Sciences level. The research method used is qualitative. The results showed (1) Strengthening social skills in the Social Sciences Training Group students could be improved through the implementation of the vision, mission, and organizational structure as well as the implementation of work programs and coaching patterns in the Social Sciences Training Group (2) Social skills that grew in the Social Sciences Training Group, namely competence religious, organizational, social, and personality. Activities to develop social skills are carried out by increasing the tri Bina. Strengthening social skills in students must be supported by the activeness and potential development of members in the Social Sciences Training Group. Mahasiswa diharapkan mampu mengembangkan keterampilan sosial sebagai bekal untuk dunia kerja selanjutnya. Gugus Latih Ilmu Sosial merupakan organisasi yang di bidang pendidikan kepramukaan yang ada di tingkat Fakultas Ilmu Sosial. Metode penelitian yang digunakan adalah metode kualitatif. Hasil penelitian menunjukkan (1)Penguatan keterampilan sosial pada mahasiswa Gugus Latih Ilmu Sosial dapat ditingkatkan melalui penerapan visi misi, struktur organisasi, pelaksanaan program kerja dan pola pembinaan di Gugus Latih Ilmu Sosial (2)Keterampilan sosial yang tumbuh di Gugus Latih Ilmu Sosial yaitu kompetensi religius, keorganisasian, sosial, dan kepribadian. Kegiatan mengembangkan keterampilan sosial dilakukan dengan meningkatkan tri bina. Penguatan keterampilan sosial pada mahasiswa harus didukung dengan keaktifan dan pengembangan potensi anggota di Gugus Latih Ilmu Sosial.